Evaluation of ligninolytic enzymes of (coptotermes curvignathus) gut bacteria for oil palm residues biodelignification - Oluwatosin Fadilat, Ayeronfe (2018)
Lignin degradation is imperative for the maximum utilization of cellulose either for pulp processing or biofuel production. Conventional methods employed in dissolving lignin involve the use of chemicals and bleaching agents with the release of highly toxic effluents, which have deleterious effects on the environment. This research aims to identify alternative method for delignification by utilizing lignin degrading enzymes secreted by the termite gut bacteria, and also to explore the green delignification of oil palm residues for sustainable pulping. The lignin degrading bacteria (LDB) from the termite gut were isolated and the lignin degrading enzymes (LDE) from the LDB cultures in kraft lignin-induced media was expressed. Bacterial growth rates were determined by measuring OD600 of grown cultures, while the LDE activity was determined using specific substrates. Chemical characterizations (Hollocellulose, cellulose, hemicellulose and lignin) of the oil palm residues were conducted according to relevant standard methods to explore the suitability of the residues for paper production. The oil palm residues were bio-treated with the LDB to determine their delignification efficiency. Three potential lignin degraders identified as Bacillus cereus, Lysinibacillus pakistanensis and Acinetobacter iwoffi were isolated. Peak growth was observed in culture of Lysinibacillus pakistanensis. Lysinibacillus pakistanensis, a novel lignin degrader showed highest manganese peroxidase (76.36 ± 15.74 U/L) and laccase activity (70.67 ± 16.82 U/L), while maximal activity of lignin peroxidase (262.49 ± 0.92 U/L) was recorded in culture supernatants of Bacillus cereus. Empty fruit bunch (EFB) had the highest holocellulose and cellulose contents, compared to and in oil palm trunk (OPT) and oil palm leaf (OPL) respectively. These parameters are important determinants of pulp quality and yield. In contrast, empty fruit bunch had the least hemicellulose content. The lignin content of OPL was highest as compared to EFB and OPT. Highest growth rates of the bacterial strains, as well as peak enzymes activity was observed in oil palm leaf-induced medium in all residues studied. Maximum lignin loss was observed in oil palm trunk bio-treated with Acinetobater iwoffi. The lignin degrading potential of these bacterial strains can be explored in the valorization of lignocellulosic biomass in industrial processes such as pulping, bioethanol production, fine chemicals and materials synthesis.